A Mixed Method Investigation to Determine Priorities for Improving Information, Interaction, and Individualization of Care Among Individuals on In-center Hemodialysis: The Triple I Study. (October 2020) - Rossum, Krista; Finlay, Juli; McCormick, Michael; Desjarlais, Arlene; Vorster, Hans; Fontaine, George; Talson, Melanie; Ferreira Da Silva, Priscila; Soroka, Kaytlynn V.; Sass, Rachelle; James, Matthew; Tong, Allison; et al.
Background: Current health systems do not effectively address all aspects of chronic care. For better self-management of disease, kidney patients have identified the need for improved health care information, interaction with health care providers, and individualization of care. Objective: The Triple I study examined challenges to exchange of information, interaction between patients and health care providers and individualization of care in in-center hemodialysis with the aim of identifying the top 10 challenges that individuals on in-center hemodialysis face in these 3 areas. Design: We employed a sequential mixed methods approach with 3 phases: 1. A qualitative study with focus groups and interviews (Apr 2017 to Aug 2018); 2. A cross-sectional national ranking survey (Jan 2019 to May 2019); 3. A prioritization workshop using a modified James Lind Alliance process (June 2019) Setting: In-center hemodialysis units in 7 academic centers across Canada: Vancouver, Calgary, Edmonton, Winnipeg, Ottawa, Montreal, and Halifax. Participants: Individuals receiving in-center hemodialysis, their caregivers, and health care providers working in in-center hemodialysis participated in each of the 3 phases. Methods: In Phase 1, we collected qualitative data through (1) focus groups and interviews with hemodialysis patients and their caregivers and (2) individual interviews with health care providers and decision makers. Participants identified challenges to in-center hemodialysis care and potential solutions to these challenges. In Phase 2, we administered a pan-Canadian cross-sectional ranking survey. The survey asked respondents to prioritize the challenges to in-center hemodialysis care identified in Phase 1 by ranking their top 5 topics/challenges in each of the 3 "I" categories. In Phase 3, we undertook a face-to-face priority setting workshop which followed a modified version of the James Lind Alliance priority setting workshop process. The workshop employed an iterative process incorporating small and large group sessions during which participants identified, ranked, and voted on the top challenges and innovations to hemodialysis care. Four patient partners contributed to study design, implementation, analysis, and interpretation. Results: Across the 5 participating centers, we conducted 8 focus groups and 44 interviews, in which 113 participants identified 45 distinct challenges to in-center hemodialysis care. Subsequently, completion of a national ranking survey (n = 323) of these challenges resulted in a short-list of the top 30 challenges. Finally, using small and large group sessions to develop consensus during the prioritizing workshop, 38 stakeholders used this short-list to identify the top 10 challenges to in-center hemodialysis care. These included individualization of dialysis-related education; improved information in specific topic areas (transplant status, dialysis modalities, dialysis-related complications, and other health risks); more flexibility in hemodialysis scheduling; better communication and continuity of care within the health care team; and increased availability of transportation, financial, and social support programs. Limitations: Participants were from urban centers and were predominately English-speaking. Survey response rate of 31.5% in Phase 2 may have led to selection bias. We collected limited information on social determinants of health, which could confound our results. Conclusion: Overall, the challenges we identified demonstrate that individualized care and information that improves interaction with health care providers is important to patients receiving in-center hemodialysis. In future stages of this project, we will aim to address these challenges by trialing innovative patient-centered solutions. Trial Registration: Not applicable.